Green turtle nesting activity in Penang Island from 2010 to 2016 - Mohd Salleh, Sarahaizad; Mohd Sah, Shahrul Anuar; Khan Chowdhury, Ahmed Jalal (Universiti Malaysia Terengganu, 2019)
Penang Island hosts a small nesting population of green turtles compared to other sites in Malaysia. Therefore, the objective of this study is to investigate the nesting activity of the turtles in Penang Island from 2010 to 2016 and compare them with a previous study that reported similar data from 2000 to 2009. The nesting data provided by various institutions and government departments, including the Kerachut Turtle Conservation Centre, were analyzed from January 2010 to December 2016. Results showed that 383 cumulative nestings were recorded throughout the 84 months of study, which averaged to around 54.71 nestings yearly. There was a reduction of nesting grounds from 13 to seven. These findings provide up-to-date status on the nesting statistics of green turtles in Penang Island.